Necrotizing Funisitis as an Intrauterine manifestation of Cryopyrin-Associated Periodic Syndrome: a case report and review of the literature - Kyoko Yokoi; Sachiko Minamiguchi; Yoshitaka Honda; Mizuho Kobayashi; Satoru Kobayashi; Ryuta Nishikomori (BMC, 2021)
Abstract Background Cryopyrin-associated periodic syndrome (CAPS) is a life-long, autoinflammatory disease associated with a gain-of-function mutation in the nucleotide-binding domain, leucine-rich repeat family, pyrin domain containing 3 (NLRP3) gene, which result in uncontrolled production of IL-1β and chronic inflammation. Chronic infantile neurologic cutaneous and articular (CINCA) syndrome/neonatal-Onset multisystem inflammatory disease (NOMID) is the most severe form of CAPS. Although the first symptoms may be presented at birth, there are few reports on the involvement of the placenta and umbilical cord in the disease. Therefore, we present herein a preterm case of CINCA/NOMID syndrome and confirms intrauterine-onset inflammation with conclusive evidence by using fetal and placental histopathological examination. Case presentation The female patient was born at 33weeks of gestation by emergency caesarean section and weighted at 1,514 g. The most common manifestations of CINCA/NOMID syndrome including recurrent fever, urticarial rash, and ventriculomegaly due to aseptic meningitis were presented. She also exhibited atypical symptoms such as severe hepatosplenomegaly with cholestasis. The genetic analysis of NLRP3 revealed a heterozygous c.1698 C > G (p.Phe566Leu) mutation, and she was diagnosed with CINCA/NOMID syndrome. Further, a histopathological examination revealed necrotizing funisitis, mainly inflammation of the umbilical artery, along with focal neutrophilic and lymphocytic villitis. Conclusions The necrotizing funisitis, which only involved the artery, was an unusual observation for chorioamnionitis. These evidences suggest that foetal inflammation, probably due to overproduction of IL-1β, caused tissue damage in utero, and the first symptom of a newborn with CINCA/NOMID.